Pengaruh Culture Shock, Human Relation, Dan Efikasi Diri Terhadap Penyesuaian Diri Mahasiswa Maluku Utara Di Daerah Istimewa Yogyakarta - Jakia Iskandar; Bangun Putra Prasetya (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to determine the influence of culture shock, human relations, and self-efficacy on the adjustment of students from North Maluku in Yogyakarta. The method used is quantitative with primary data, and the population consists of all North Maluku students in Yogyakarta. Data analysis was conducted using multiple linear regression with the equation Y = 5.855 + 0.258X1 - 0.325X2 + 0.804X3 + 1.219. The F-test results show = 56.825 > = 3.09 (sig = 0.000 < 0.05), indicating that the three variables simultaneously have a significant effect on student adjustment. The t-test results show that culture shock ( = 2.677 > = 1.984) and self-efficacy ( = 5.792 > = 1.984) have a significant effect, while human relations ( = -2.246 < = 1.984) do not have a significant effect.